(+)-/(−)-Rutabenzofuran A and (+)-/(−)- Rutabenzofuran B: Two unprecedented pairs of Z/E isomeric benzofuran enantiomers from the aerial part of Ruta graveolens L. (June 2023) - Liu, Yanyang; Peng, Jing; Huang, Ling; Li, Bichen; Ge, Chengyu; Liu, Shao; Jiang, Yueping
Abstract: Two pairs of Z/E isomeric benzofuran enantiomers possessing unprecedented carbon skeletons featuring ring cleavage and addition reactions in the α -pyrone ring of furocoumarin, named rutabenzofuran A [(+)-1 and (−)-1 ], and rutabenzofuran B [(+)-2 and (−)-2 ], respectively, were isolated as minor compounds from the water extract of the aerial part of Ruta graveolens L. Their structures were determined by extensive spectroscopic data analysis. The absolute configurations were assigned by comparing the optical rotation with previous research and the experimental circular dichroism (CD) spectra with the calculated electronic CD (ECD) spectra. (−)-1, (+)-2, and (−)-2 were evaluated for antibacterial, anticoagulant, anticancer, and acetylcholinesterase (AChE) inhibitory activities. No anticancer or anticoagulant activities were observed, yet (−)-2 exhibited weak antibacterial activity against Salmonella enterica subsp. Enterica . At the same time, (−)-1, (+)-2, and (−)-2 displayed weak inhibitory activity on AChE. Graphical abstract: Two pairs of Z/E isomeric benzofuran enantiomers possessing unprecedented carbon skeletons were isolated from the water extract of the aerial part of Ruta graveolens L. Image 1 Highlights: Z/E isomeric benzofuran enantiomers were isolated from Ruta graveolens L. The four compounds possessing undescribed carbon skeletons. Hypothetical biosynthetic pathways of the four compounds were proposed. Several bioactivity assessments were conducted.